2019
DOI: 10.1002/qua.26147
|View full text |Cite
|
Sign up to set email alerts
|

Molecular design of novel indacenodithiophene‐based organic dyes for efficient dye‐sensitized solar cells applications

Abstract: Indacenodithiophene (IDT)‐based high‐efficiency photovoltaics have received increasing attention recently. This paper reports a density functional theory investigation of the electronic and optical properties of three IDT‐based organic dyes together with the dye/(TiO2)46 interface. In order to enhance the photoelectric properties of IDT dyes, this paper considers two methods for the structure modification of the experimentally reported dye DPInDT (J. Org. Chem. 2011, 76, 8977): the extension of the conjugation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 55 publications
(98 reference statements)
0
1
0
Order By: Relevance
“…Continuous growth of research interest in oligothiophene systems is observed due to their wide range of applications as organic photoelectric devices and optical materials. [ 1–4 ] These thiophene‐based materials make significant contributions, especially in the field of light‐emitting diodes, [ 5,6 ] photovoltaics, [ 7,8 ] and organic field‐effect transistors. [ 9,10 ] Stability, suitable highest occupied molecular orbital‐lowest unoccupied molecular orbital (HOMO‐LUMO) energy gap, strong optical absorption in a desired region, and suitable bandgap are among the few requirements of molecular systems for applications as efficient photoelectric devices.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous growth of research interest in oligothiophene systems is observed due to their wide range of applications as organic photoelectric devices and optical materials. [ 1–4 ] These thiophene‐based materials make significant contributions, especially in the field of light‐emitting diodes, [ 5,6 ] photovoltaics, [ 7,8 ] and organic field‐effect transistors. [ 9,10 ] Stability, suitable highest occupied molecular orbital‐lowest unoccupied molecular orbital (HOMO‐LUMO) energy gap, strong optical absorption in a desired region, and suitable bandgap are among the few requirements of molecular systems for applications as efficient photoelectric devices.…”
Section: Introductionmentioning
confidence: 99%